2004
DOI: 10.1111/j.0143-2885.2004.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of apical periodontitis and frequency of root‐filled teeth in an adult Spanish population

Abstract: The prevalence of AP in root-filled and untreated teeth, and the frequency of root-filled teeth were comparable to those reported in previous similar studies carried out in European countries. The prevalence of root-filled teeth with AP was found to be higher compared to that demonstrated in other epidemiological studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

30
162
16
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 173 publications
(226 citation statements)
references
References 28 publications
(171 reference statements)
30
162
16
10
Order By: Relevance
“…Previous surveys that have reported similar results explained this gender discrepancy as occurring because women have a greater interest in receiving dental care. 19,20 The present study showed a significant difference in AP between men (37.59%) and women (62.41%) (p < 0.05), which may be explained by the smaller number of males in this sample.…”
Section: Discussioncontrasting
confidence: 47%
See 4 more Smart Citations
“…Previous surveys that have reported similar results explained this gender discrepancy as occurring because women have a greater interest in receiving dental care. 19,20 The present study showed a significant difference in AP between men (37.59%) and women (62.41%) (p < 0.05), which may be explained by the smaller number of males in this sample.…”
Section: Discussioncontrasting
confidence: 47%
“…7,13,19,20,21 The results presented herein revealed that the prevalence of apical periodontitis among teeth with previous endodontic treatment or teeth referred for endodontic treatment was highest in the 40-49 age group, followed by the 30-39 age group. Both the 50-59 and the 60+ age groups contained fewer patients with AP.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations